2002
DOI: 10.1159/000065990
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Course and Outcome in Hypochondriasis after Cognitive-Behavioral Treatment

Abstract: Background: Predictors of treatment outcome were evaluated in a clinical sample suffering from hypochondriasis. Methods: The sample consisted of 96 patients with hypochondriacal disorder according to DSM-IV or high syndrome scores on the Illness Attitude Scales (IAS) or Whiteley Index (WI). After intense inpatient cognitive-behavioral treatment (CBT), 60% of the patients were classified as responders because of substantial improvements or recovery from hypochondriacal symptomatology. Results: Non-responders we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…These findings corresponds with earlier studies of outcome for headache patients [25][26][27] and a study of hypochondriasis, which showed more somatisation among non-responders [28]. In the present study most patients were offered 8 group sessions focused on different relaxation techniques and behavioural and cognitive stress management.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings corresponds with earlier studies of outcome for headache patients [25][26][27] and a study of hypochondriasis, which showed more somatisation among non-responders [28]. In the present study most patients were offered 8 group sessions focused on different relaxation techniques and behavioural and cognitive stress management.…”
Section: Discussionsupporting
confidence: 92%
“…The corresponding numbers for the different headache diagnoses were TTH 26 , , and Other 29 (21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Resultsmentioning
confidence: 99%
“…In a study [38] on intense inpatient cognitive-behavioural therapy for hypochondriasis, the pretreatment IAS total score significantly predicted the clinical outcome, as identified by the IAS total score measured at discharge and at a 2-year follow-up, and the degree of change in this score between pretreatment and follow-up. Unlike the WI, which failed to discriminate between responders and non-responders, the pretreatment IAS total score was significantly higher in the latter.…”
Section: Resultsmentioning
confidence: 99%
“…Only a few studies have investigated which predictors are associated with a favorable treatment outcome in hypochondriasis, and to our knowledge only on the short term. These studies showed that good treatment outcome seems to be negatively associated with illness duration, comorbidity, severity of pre-treatment hypochondriasis, extent of somatization symptoms, general psychopathology, dysfunctional cognitions related to bodily functioning, psychosocial impairments, utilization of the health care system and benzodiazepine use (Greeven et al, 2007;Hiller, Leibbrand, Rief, & Fichter, 2002;Kellner, 1983). The counterproductive effect of benzodiazepine use can be explained by its relation to anxiety sensitivity.…”
Section: Introductionmentioning
confidence: 99%